Composite Cardiovascular Outcomes in Patients With Primary Aldosteronism Undergoing Medical Versus Surgical Treatment: A Meta-Analysis - Huang, Wei-Chieh; Chen, Ying-Ying; Lin, Yen-Hung; Chueh, Jeff S. (Frontiers in Endocrinology, 2021)
Background Superior performance outcomes of after surgical treatment over medical treatment for lateralized primary aldosteronism (PA) has been reported in small-scale clinical studies with diverse clinical outcomes, but no solid conclusion has been drawn as results of large randomized trials are lacking. Methods We performed a search of PubMed, MEDLINE, Embase and Cochrane Library for randomized or observational studies that investigated cardiovascular outcomes in patients with primary aldosteronismPA undergoing medical versus surgical treatment. Meta-analyses of both composite and individual outcomes were conducted. Risks of bias of the included studies were assessed with Risk Of Bias In Non-randomized Studies of Interventions (ROBINS-I) checklist. Trial sequential analysis (TSA) was performed to control the risk of random errors and assess whether the results in our meta-analysis were conclusive. Results A total of 121 studies, including a total of 6148 PA patients, were included in the meta-analysis. The results of meta-analyses demonstrated lower incidence of composite cardiovascular outcomes among PA patients who underwent surgical treatment over medical treatment (Odds Ratio (OR): 0.49). Surgical treatment also led to less incidence of persistence of HT hypertension (OR of non-cure of HThypertension: 0.31). Fewer major cardiovascular events and mortality events after surgical treatment were observed in the fixed effect model (OR: 0.6047). after surgical treatment. TSA result showed that the required information size was 2151 and the cumulative Z curve crossed the futility boundary and reached the required information size. Conclusion: Superior performance of surgical treatment over medical treatment is confirmed with meta-analyses in terms of lower incidences of composite cardiovascular outcomes and non-cure of HThypertension. Hence, adrenalectomy could now be concluded as the treatment of choice for lateralized PA.